4G/5G antenna system with dual function planar connected array. Issue 12 (17th August 2017) - Ikram, Muhammad; Hussain, Rifaqat; Sharawi, Mohammad S.
Abstract : An integrated design consisting of a multiple‐input‐multiple‐output (MIMO) antenna system forfourth generation applications and a planar connected array (PCA) for fifthgeneration applications is presented. The proposed design contains a 4‐elementprinted‐inverted‐F antenna‐based MIMO antenna system and a slot‐based PCA. Theantenna system is fabricated on a commercially available RO‐4350 substrate with ϵ r equal to 3.5. The dimensions of the boardare 100 × 60 × 0.76 mm 3 representing a typical smart phone backplanesize. The antenna system covers 2.1 and 12.5 GHz frequency bands via its MIMOand PCA parts, respectively. The design is planar, low profile and compact instructure that is suitable for wireless handheld devices and mobile terminals.The PCA also serves as a defected ground structure at 2.1 GHz thus having twofunctions. Isolation is improved by at least 4 dB. The PCA consists of a 4 × 3radiating slots fed via a corporate feed structure. The measured gain andefficiency values at the centre frequency are at least 3.4 dBi and 74%, respectively, for the MIMO antenna system and 8 dBi and 80% for the PCA. Theenvelope correlation coefficient did not exceed 0.2824 for all antennas showinggood MIMO performance.